Unusual form of strongyloidiasis with gastric involvements: A case report - Soheil Ebrahimpour; Mahmoud Sadeghi–Haddad–Zavareh; Zeinab Darabi Ahangar; Zeinab Mohseni Afshar; Zeinab Sheidaie; Parisa sabbagh; Arefeh Babazadeh (Journal of Acute Disease, 2019)
Rationale: Strongyloides stercoralis (S. stercoralis) is an intestinal nematode with a complicated life cycle that can involve the gastrointestinal system. Infected patients are generally asymptomatic; but if symptomatic, the symptoms will include skin rash, respiratory and gastrointestinal symptoms like abdominal pain, diarrhea, nausea and vomiting. Patient concerns: A 77-year old man presented with edema of the lower extremities and insignificant tenderness in the epigastric region. Diagnosis: The histopathology of gastric tissue showed severe inflammation and multiple ulcers in the cardia, antrum and proximal duodenum. A large number of rhabditiform larvae of S. stercoralis along with tissue hyperemia and infiltration of lymphoplasma cells, eosinophils, and neutrophils were found. Intervention: Treatment with albendazole. Outcome: Despite the albendazole treatment, the patient’s condition deteriorated and eventually died because of a sepsis-like syndrome. Lesson: Physicians should remain alert to the urgency due to threadworm, especially among the elderly people and immunosuppressed cases; and should ensure accurate diagnosis, suitable treatment and careful follow-up of these cases.